Tackler and ball-carrier technique during moderate and severe injuries (≥8 days lost) compared with player-matched and team-matched injury-free controls in Elite Rugby Union. Issue 24 (13th July 2021) - Meintjes, Vincent; Forshaw, Pip; den Hollander, Steve; Starling, Lindsay; Lambert, Michael Ian; Viljoen, Wayne; Readhead, Clint; Hendricks, Sharief
Abstract : Objective: To analyse tackler and ball-carrier technical proficiency during moderate and severe contact injuries (≥8 days lost) in professional rugby union, and compare it with injury-free event-matched controls from the same player and from the same team. Methods: Technical proficiency for 74 (n=74) (moderate and severe; ≥8 days lost) tackler and ball-carrier injuries during The Currie Cup (2014–2018) and 623 matched non-injury events (253 own controls, 370 team controls) were examined through video analysis using a standardised list of technical criteria. Results: Mean technical proficiency score for injured tacklers during front-on tackles was 6.19/16 (arbitrary units (AU) 95% CI 4.89 to 7.48), which was significantly different to their own controls (8.90/16 AU, 95% CI 8.37 to 9.43, p<0.001, effect size (ES)=1.21, large) and team controls (9.93/16 AU, 95% CI 9.50 to 10.40, p<0.001, ES=1.71, large). Mean technical proficiency score for injured ball-carriers during front-on tackles was 5.60/14 AU (95% CI 4.65 to 6.55), which was significantly different to their own controls (8.08/14 AU, 95% CI 7.56 to 8.60, p<0.001, ES=1.16, moderate) and team controls (8.16/14 AU, 95% CI 7.75 to 8.57, p<0.001, ES=1.25, large). Conclusion: For the tackler and ball-carrier, for both front-on and side-on/behind tackles, overall technical proficiency scores were significantly lower for the injury-causing event, when compared with the player's own injury-free tackles and the team's injury-free tackles. Through analysing player and team controls, player technique deficiencies for the injured player and player technique deficiencies that expose all players to injury were highlighted, which may inform injury prevention strategies and policies, and assist coaches in optimising training to reduce tackle injury risk.